PENGEMBANGAN MODUL PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN SAINTIFIK - Ila Ritanti; Ahde Fitri (Mat-Edukasia, 2021)
The purpose of this study is to develop a learning module with a scientific approach to valid and practical number pattern material, by going through the stages or steps of a scientific approach in the form of observing, asking questions, gathering information, reasoning, and communicating. The development procedure used in this research is the 4-D model consisting of 4 stages, namely the define stage, the design stage, the develop stage, and the dissemination stage. The results of this development are seen from the results of module validation and module practicality. The module is validated by 5 validators consisting of 2 mathematical material experts, 1 linguist, one design expert and one mathematics subject teacher for class VIII MTs Al-Munawwaroh. The result of the whole module validation with the scientific approach that has been carried out shows an average score of 4.42 with a very valid category. While the practicality of the module is seen from the results of the practicality questionnaire that were tested by all 15 students of MTs Al-Munawwaroh showing that the module with the scientific approach produced is very practical with a result of 97.85%. Based on the results of the study, it was found that the module with a scientific approach on the number pattern material developed could be used and was feasible for use in MTs Al-Munawwaroh